Reservoir Engineering Models : Analytical and Numerical Approaches - Ertekin,Turgay; Ayala, Luis F. (McGraw-Hill's AccessEngineering., 2019)
Develop, build, and deploy accurate mathematical models for hydrocarbon reservoirs. This practical resource discusses the construction of reservoir models as well as their implementation in both forward and inverse modes using numerical, analytical, empirical, and artificial intelligence techniques. Written by a pair of experts in the field, Reservoir Engineering Models: Analytical and Numerical Approaches clearly explains the complicated building processes of mathematical models and lays out cutting-edge solution protocols. Advanced chapters teach the assembly of complex physical processes using principles of physics, thermodynamics, and mathematics. You will learn to optimize decision-making processes applicable to the management of field development and extraction activities. Coverage includes: ? An introduction to the fundamentals of reservoir engineering ? Background on mathematics and transport equations ? Hydrocarbon fluid models and thermodynamics ? Analytical and numerical reservoir engineering solutions ? Proxy and hybrid models.